Plessner's Philosophical Anthropology : Perspectives and Prospects - Mul, Jos de, 1956-; Project Muse. (Amsterdam : Amsterdam University Press, 2014)
The work of the German philosopher Helmuth Plessner (1892-1985) inspired generations of scholars and has been enjoying a recent renaissance. This volume offers the first substantial English-language introduction to Plessner's philosophical anthropology, contextualising it by comparison with the more familiar contemporaries such as Bergson, Cassirer and Merleau-Ponty, but also showing his relevance to contemporary discussion in a variety of scholarly fields.
Helmuth Plessner (1892-1985) was one of the founders of philosophical anthropology, and his book The Stages of the Organic and Man, first published in 1928, has inspired generations of philosophers, biologists, social scientists, and humanities scholars. This volume offers the first substantial introduction to Plessner's philosophical anthropology in English, not only setting it in context with such familiar figures as Bergson, Cassirer, and Merleau-Ponty, but also showing Plessner's relevance to contemporary discussions in a wide variety of fields in the humanities and sciences.
1. Philosophical Anthropology -- 2. The Nascence of Modern Man -- 3. "True" and "False" Evolutionism -- 4. Life, Concept and Subject -- 5. Bodily Experience and Experiencing One's Body -- 6. Plessner and the Mathematical-Physical Perspective -- 7. The Body Exploited -- 8. Plessner's Theory of Eccentricity -- 9. The Duty of Personal Identity -- 10. Anthropology as a Foundation of Cultural Philosophy -- 11. Bi-Directional Boundaries -- 12. The Unbearable Freedom of Dwelling -- 13. Eccentric Positionality and Urban Space -- 14. Strangely Familiar -- 15. De-Masking as a Characteristic of Social Work? -- 16. Helmuth Plessner as a Social Theorist -- 17. Habermas's New Turn towards Plessner's Philosophical Anthropology -- 18. The Quest for the Sources of the Self, Seen from the Vantage Point of Plessner's Material a Priori -- 19. The Brain in the Vat as the Epistemic Object of Neurobiology -- 20. Switching "On," Switching "Off" -- 21. On Humor and "Laughing" Rats -- 22. A Moral Bubble -- 23. Eccentric Positionality as a Precondition for the Criminal Liability Of Artificial Life Forms -- 24. Not Terminated -- 25. Plessner and Technology -- 26. Philosophical Anthropology 2.0 -- About the Authors -- Name Index -- Subject Index.
A selection of the papers presented at the IVth International Plessner Conference, held at the Erasmus University Rotterdam in 2009.
English.
Description based on print version record.
Keywords: Plessner, Helmuth, -- 1892-1985.; Plessner, Helmuth, -- 1892-1985 -- Stufen des Organischen und der Mensch -- Congresses; Philosophical anthropology; Biology -- Philosophy; Philosophy / History & Surveys / Modern; Western philosophy, from c 1900.; Philosophy; Humanities; History of Western philosophy; Biologie -- Philosophie -- Congres; Anthropologie philosophique -- Congres; Biologie -- Philosophie -- Congres; Anthropologie philosophique -- Congres; Biology -- Philosophy -- Congresses; Philosophical anthropology -- Congresses; Biology -- Philosophy -- Congresses; Philosophical anthropology -- Congresses; Conference papers and proceedings; Electronic books; Electronic books